2015
DOI: 10.1002/jssc.201500172
|View full text |Cite
|
Sign up to set email alerts
|

Determination of chlorophenols in red wine using ionic liquid countercurrent chromatography as a new pretreatment method followed by high-performance liquid chromatography

Abstract: A countercurrent chromatography method for the enrichment and cleanup of chlorophenols from food samples was successfully established by using an ionic-liquid-modified two-phase solvent system composed of dichloromethane containing 2% 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and water. The column was firstly filled with the organic stationary phase, and then a large volume of sample was pumped into the column after it was equilibrated with pure water at the rotation speed. Finally, the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The polyphenolic profile (together with other classes of compounds) in tea or coffee extracts has also been explored with the use of LLC (Fan et al, 2022; Si et al, 2006; Stodt et al, 2015; Yanagida et al, 2006; Yuan et al, 2004). LLC has also been applied in separating polyphenols from red wine and rum aged in oak barrels (Fan et al, 2015; Regalado et al, 2011). Furthermore, LLC has been employed to examine the polyphenols composition of numerous fruits, that is, blackcurrants (He et al, 2009; Mbeunkui et al, 2012), citrus fruits (Rodríguez‐Rivera et al, 2014; Zhu et al, 2013), apples (Castillo‐Fraire et al, 2019; Lu et al, 2019), or passion fruit (Pan et al, 2020).…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…The polyphenolic profile (together with other classes of compounds) in tea or coffee extracts has also been explored with the use of LLC (Fan et al, 2022; Si et al, 2006; Stodt et al, 2015; Yanagida et al, 2006; Yuan et al, 2004). LLC has also been applied in separating polyphenols from red wine and rum aged in oak barrels (Fan et al, 2015; Regalado et al, 2011). Furthermore, LLC has been employed to examine the polyphenols composition of numerous fruits, that is, blackcurrants (He et al, 2009; Mbeunkui et al, 2012), citrus fruits (Rodríguez‐Rivera et al, 2014; Zhu et al, 2013), apples (Castillo‐Fraire et al, 2019; Lu et al, 2019), or passion fruit (Pan et al, 2020).…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Since the initial work of Berthod et al in ILLC, there have been a number of papers describing the use of ionic liquids in CCC. These include the analysis of mycotoxins [ 119 ] and chlorophenols in red wines [ 120 ], the potential use of aqueous biphasic solvent systems containing ionic liquids in the separation of caffeine from xanthine and nicotine [ 121 ] and in the separation of neomangiferin and mangiferin from Rhizoma anemarrhenae , all using the hydrolytically unstable [C 4 mim][PF 6 ] [ 107 ] as an additive to aqueous ethyl ethanoate [ 122 ].…”
Section: Ionic Liquids In Chromatographymentioning
confidence: 99%
“…We have also reported that A. alternata strains have the ability to produce TA on detached Malbec wine grapes and the natural occurrence of TA in economically important red wine grape varieties from Argentina as Malbec, Cabernet Sauvignon and Syrah grapes (Fontana et al 2016;Prendes et al 2018b). Additionally, there are numerous studies reporting the natural occurrence of AOH, AME and TA on grape juices and wine (Scott et al 2006;Broggi et al 2013;Pizzutti et al 2014;Fan et al 2016;L opez et al 2016). Given that Alternaria toxins exposure has been linked to a great variety of adverse effects to both human and animal health (Dall'Asta et al 2014), its regulation on food is currently a concern (Alexander et al 2011;Arcella et al 2016).…”
Section: Introductionmentioning
confidence: 99%